Regional Features of Organizing Economic Clusters - Kadirov , San’at (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article discusses the need for the formation of economic clusters, their specific priorities and their regional characteristics. It also provides a conclusion on the study of the regional characteristics of the formation of economic clusters.